Sacred nature - Mesner, Aljaž (Svetovi (Ljubljana), 2024)
This paper explores the role of Shinto in Japanese environmentalism. It first presents perceptions of nature in Japan and the historical role of Shinto, then delves into the conservation of sacred shrine forests – Chinju no mori – within the Shinto environmentalist discourse. The role of Shinto in politics is demonstrated through the activities of the Association of Shinto Shrines – Jinja Honcho. Finally, presenting shrine groves as urban green spaces and community centres shows the potential of Shinto values working together with environmental conservation.
Keywords: Chinju no mori; environmentalism; Japan; Japonska; narava; nature; politics; politika; religija; religion; Shinto; šintoizem; varstvo okolja